Two-sided friction stir riveting by extrusion: A process for joining dissimilar materials. (August 2016) - Evans, William T.; Cox, Chase; Gibson, Brian T.; Strauss, Alvin M.; Cook, George E.
Abstract: Two-sided friction stir riveting (FSR) by extrusion is an innovative process developed to rapidly, efficiently, and securely join dissimilar materials. This process extends a previously developed one sided friction stir extrusion process to create a strong and robust joint by producing a continuous, rivet-like structure through a preformed hole in one of the materials with a simultaneous, two-sided friction stir spot weld. The two-sided FSR by extrusion process securely joins the dissimilar materials together and effectively locks them in place without the use of any separate materials or fasteners. In this paper we demonstrate the process by joining aluminum to steel and illustrate its potential application to automotive and aerospace manufacturing processes.